Moral Conformity through the Lens of Bibliometric and Content Analysis - Marina V. Zlobina; Alexandr A. Fedorov (Peoples' Friendship University of Russia (RUDN University), 2023)
The purpose of this study is to make a bibliometric and content analysis of publications on the problem of moral conformity. Its relevance is due to the emerging interest in this phenomenon. The materials under study were publications in English extracted from the Scopus and Google Scholar databases as well as Google Ngram data. The data were processed using the VOSviewer program and the bibliometrix R-package. It was shown that for the period from 1800 to 2019 the proportion of texts containing the term 'moral conformity' increased significantly in comparison with texts containing the term 'conformity'. A term map constructed using the Google Scholar database made it possible to identify four clusters, reflecting four areas in which the concept 'moral conformity' was found. A bibliometric analysis of the concept 'moral conformity' in the field of psychology highlighted four clusters that reflected the main aspects of this phenomenon. A keyword frequency analysis over time showed that since 2007 the frequency of use of the concepts 'morality' and 'conformity' had noticeably increased. A content analysis of publications revealed 10 sources directly related to the phenomenon of moral conformity. Recent studies have indicated that this phenomenon is quite stable and manifests itself in different samples and in different conditions. On the whole, the problem of moral conformity is quite new and requiring additional examine. One possible direction for further research can be aimed at verifying the results of previous studies on a Russian-speaking sample or studying the phenomenon under conditions of both real and virtual pressure.